Burnout among nurses: a multicentric comparative study - Elisabete Maria das Neves Borges; Cristina Maria Leite Queirós; Margarida da Silva Neves de Abreu; Maria Pilar Mosteiro-Diaz; Maria Baldonedo-Mosteiro; Patrícia Campos Pavan Baptista; Vanda Elisa Andres Felli; Miriam Cristina dos Santos Almeida; Silmar Maria Silva
Objetivo: to identify and compare burnout levels between Portuguese, Spanish and Brazilian nurses. Method: quantitative, descriptive, correlational, comparative and cross-sectional study conducted using a sample of 1,052 nurses working in hospitals and primary care centers. A sociodemographic questionnaire and the Maslach Burnout Inventory were applied to nurses in Porto, Portugal (n=306), Oviedo, Spain (n=269) and S. Paulo, Brazil (n=477). Data analysis was performed using descriptive, inferential and multivariate analysis. Results: approximately 42% of the nurses showed moderate/high levels of burnout, with no differences found between countries (Portugal and Brazil 42%, Spain 43%). Only depersonalization showed differences between countries, presenting Spain the highest level and Portugal the lowest one. Comparative analysis showed higher burnout levels in young nurses and those working by shifts. Considering job schedules, burnout was associated to shift work in Portugal, while in Spain and Brazil it was associated with fixed schedules. Conclusion: these results suggest that this syndrome among nurses is a global phenomenon. The daily stressors and higher demands of the nursing profession are crucial in the preparation of nurses to deal with complex situations, to avoid burnout, and to reduce the negative impact on nurses' health and on the quality of care they provide.